Developing Perception-Based Themes for Assessing Peri-Urban Landscape Elements - Mat Isa, Masbiha; Nor Atiah Ismail; Noor Fazamimah Mohd Ariffin (Journal of Social Transformation and Regional Development, 2025)
Peri-urban areas in developing countries are increasingly vulnerable to rapid development, which transforms their distinctive physical landscape elements. Identifying which elements are most exposed to change is essential for effective planning, management, and conservation. However, systematic and validated approaches for capturing these elements from community perspectives remain limited, particularly in peri-urban contexts. This study aimed to develop and validate a set of themes that could guide the construction of reliable questionnaires for assessing changes in peri-urban landscape elements within the context of Asia and Oceania. Drawing on the concepts of landscape character, land use change, and peri-urban development, a systematic literature review was conducted to identify relevant articles. Selected articles were coded and analysed using Atlas. ti, producing eight initial themes and 42 sub-themes, which were subsequently refined through expert evaluation into five key themes: landforms, natural vegetation, water bodies, agriculture, and heritage. These validated themes serve as a robust conceptual foundation for questionnaire development, ensuring that subsequent instruments are both context-specific and methodologically sound. In doing so, the study not only advances the methodological basis for peri-urban research but also offers practical guidance for scholars and practitioners seeking to design evidence-based tools for planning and regional development.